The AXIOM platform for next-generation cyber physical systems - Theodoropoulos, Dimitris; Mazumdar, Somnath; Ayguade, Eduard; Bettin, Nicola; Bueno, Javier; Ermini, Sara; Filgueras, Antonio; Jiménez-González, Daniel; Álvarez Martínez, Carlos; Martorell, Xavier; Montefoschi, Francesco; Oro, David; et al. (Microprocessors and microsystems, 2017)
Cyber-Physical Systems (CPSs) are widely used in many applications that require interactions between humans and their physical environment. These systems usually integrate a set of hardware-software components for optimal application execution in terms of performance and energy consumption. The AXIOM project (Agile, eXtensible, fast I/O Module), presented in this paper, proposes a hardware-software platform for CPS coupled with an easy parallel programming model and sufficient connectivity so that the performance can scale-up by adding multiple boards. AXIOM supports a task-based programming model based on OmpSs and leverages a high-speed, inexpensive communication interface called AXIOM-Link. The board also tightly couples the CPU with reconfigurable resources to accelerate portions of the applications. As case studies, AXIOM uses smart video surveillance, and smart home living applications.